Premix insulins in type 1 diabetes: the coming of degludec/aspart. (3rd April 2019) - Rendell, Marc
ABSTRACT: Introduction : Although premixed fixed ratio NPH insulin products are commonly used in type 2 diabetes patients, the advent of Glargine insulin which cannot be formulated together with a rapid-acting insulin (basal-bolus) has largely eliminated premixed insulin from use in type 1 diabetes. Degludec insulin can be formulated together with Aspart insulin in a 70/30 fixed ratio product. We review the potential use of Degludec-Aspart in type 1 diabetes. Areas covered : A historical search of the development and use of premixed insulin preparations was performed relying on Pubmed, FDA, and European Union records. Expert opinion : Degludec is a once daily insulin. There appears to be little advantage to administration of Degludec-Aspart twice daily, and basal bolus injections have proved superior to premixed insulin in type 1 diabetes. There may still be a role for this premixed fixed ratio formulation in patients who have opted to use Technosphere inhaled insulin prior to and post meals. In such patients, the use of a single injection of Degludec-Aspart prior to the largest meal of the day might provide an anchor to allow patients to then self-administer multiple inhalations around mealtimes.